Structure and function of the musculoskeletal system - Watkins, James 1946- (Human Kinetics, 2010)
Written by James Watkins, an authority on functional anatomy, Structure and Function of the Musculoskeletal System, Second Edition, integrates anatomy and biomechanics to describe the intimate relationship between the structure and function of the musculoskeletal system. This unique reference thoroughly explores the biomechanical characteristics of musculoskeletal components and the response and adaptation of these components to the physical stress imposed by everyday activities. Following a systematic approach, Structure and Function of the Musculoskeletal System describes the basic composition and function of the musculoskeletal system; mechanical concepts and principles that underlie human movement; functional anatomy of the skeletal, connective tissue, articular, and neuromuscular systems; mechanical characteristics of musculoskeletal components; structural adaptation of musculoskeletal components; and the etiology of musculoskeletal disorders and injuries. The second edition of Structure and Function of the Musculoskeletal Systemfeatures nearly 700 detailed, full-color illustrations showing key structures and biomechanical properties of the musculoskeletal system. Elementary biomechanical concepts are incorporated throughout the text, offering readers a more integrated understanding of how forces are created and relayed by the components of the musculoskeletal system. The second edition of Structure and Function of the Musculoskeletal System also includes new information on the effects of aging on muscle function as well as a new appendix with illustrations of each muscle group and tables detailing the origin, insertion, and action of individual muscles. In addition, several new case studies illustrate the response and adaptation of the musculoskeletal system to exercise at various ages and in various situations. These case studies present current research and how the findings can be put to practical use in physical activity, competitive sport, rehabilitation, and activities of daily living. Students new to anatomy or biomechanics will benefit from the book's reader-friendly structure featuring applied examples, summaries, review questions, references, an extensive subject index, and a glossary that runs parallel to the text. Learning objectives at the beginning of each chapter identify the key topics, and interesting facts and key points are set off within highlight boxes throughout the text. Highlighted introductory figures assist readers in understanding content as they refer to a sequence of subsequent figures while reading the text. Structure and Function of the Musculoskeletal System, Second Edition, offers readers a clear conception of how the components of the musculoskeletal system coordinate to produce movement and continuously adapt their structure to the strain of everyday physical activity as well as the effects of aging. Illustrated with full-color detail, this unique resource will assist both future and current professionals in the diagnosis and treatment of musculoskeletal disorders by enhancing their understanding of the relationship between the structure and function of the musculoskeletal system.